2017
DOI: 10.1111/and.12906
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H-quinone oxidoreductase 1 silencing aggravates hormone-induced prostatic hyperplasia in mice

Abstract: NAD(P)H-quinone oxidoreductase 1 (NQO1) is a highly inducible flavoprotein known to involve in various cellular defence mechanisms. In this study, we explored whether NQO1 deletion affects hormone-induced prostatic hyperplasia. Testosterone propionate (3 mg/kg, IP) was injected into wild-type (WT) and NOQ1 knockout C57BL/6 mice (NQO1 ) for 14 consecutive days, and the samples were collected for biological and histochemical studies. The testosterone-treated NQO1 showed about 140% higher prostate weight than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This family of isomerases contains a tetratricopeptide repeat domain that allows them to interact and regulate HSP90 (Heat Shock Protein 90) 56 . Animal studies suggest that HSP90 can promote prostate hyperplasia by activating the classical complement pathway or by enhancing testosterone‐induced nuclear AR expression 57,58 . Whether these alterations are drivers or passengers in BPH progression requires more investigation; however, their increased frequency does justify that investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This family of isomerases contains a tetratricopeptide repeat domain that allows them to interact and regulate HSP90 (Heat Shock Protein 90) 56 . Animal studies suggest that HSP90 can promote prostate hyperplasia by activating the classical complement pathway or by enhancing testosterone‐induced nuclear AR expression 57,58 . Whether these alterations are drivers or passengers in BPH progression requires more investigation; however, their increased frequency does justify that investigation.…”
Section: Discussionmentioning
confidence: 99%
“…111 Kim et al reported that a deficiency of the nitroquinoline 1-oxide (NQO1) enzyme, which is an flavin adenine dinucleotide dependent flavoprotein that performs various functions in the cellular defense system, increased the expression of HSP90, which increases the affinity of AR for testosterone and can be responsible for enlargement of the prostate gland in NQO1 knockout mice. 112…”
Section: Heat Shock Proteinsmentioning
confidence: 99%
“…Another study on the role of HSP90 in the development of BPH was carried out on a murine model with induced prostate hyperplasia and on human cell lines (LNCaP, BPH-1, WPMY-1), where the role of NAD(P)H-quinone oxidoreductase 1 (NQO1) was analyzed, a FAD-dependent flavoprotein, involved in the defense processes in the cell and preventing the degradation of the p53 protein, in the exacerbation of prostate tissue cell hyperplasia [114]. This study showed that the deficiency of the NQO1 enzyme increases the expression of HSP90, which increases the affinity of AR for testosterone and can be responsible for the enlargement of the prostate gland in NQO1-/-mice.…”
Section: Hsp90 and Prostate Cancer And Benign Prostatic Hyperplasiamentioning
confidence: 99%